HEGEMONIC APPROACHES IN DISASTER RISK MANAGEMENT ASSOCIATED WITH HYDROMETEOROLOGICAL EVENTS: ANALYSIS OF THE CONTEXT OF LATIN AMERICA AND THE CARIBBEAN - Trejo-Rangel, Miguel Angel; Ribeiro, Rodrigo Rudge Ramos; Lopera, Cristian Camilo Fernández; Ferreira, Adriano Mota [UNESP]; Esquivel-Gomez, Nhilce Nahomi; Liera-Martínez, Carla Cristina (Revista de Estudios Latinoamericanos sobre Reduccion del Riesgo de Desastres, 2022)
Five of the ten most affected countries by climate-related disasters worldwide are located in the Latin American and Caribbean (LAC) region, which has incorporated Disaster Risk Management (DRM) into its development policies. Such DRM is ruled by international public policy guidelines that state financing priorities and research approaches. Thus, this study aims to identify which of the intervention approaches (especially top-down) prevail in the scientific literature as a reflection of the hegemonic discourses in DRM of the LAC region. To achieve this, a regional characterization of scientific literature on DRM was carried out through a systematic review of academic literature making use of the web-tool Rayyan. The analysis of the literature responds to a classification by type of intervention approach. The results found that most papers are based on a top-down approach, while very few studies consider a bottom-up approach. The countries with the most publications on this matter are Brazil, Mexico, and Chile. The preventive approach is the predominant and floods are the most addressed type of threat.
ENFOQUES HEGEMÓNICOS EN LA GESTIÓN DEL RIESGO DE DESASTRES ASOCIADOS A EVENTOS HIDROMETEOROLÓGICOS: ANÁLISIS DEL CONTEXTO DE LATINOAMÉRICA Y EL CARIBE
Keywords: Disaster risk management; Disasters; Hegemonic approaches; Hydrometeorological events; Latin America and the Caribbean